Writing for love and money : how migration drives literacy learning in transnational families - Vieira, Kate, 1977- (New York, NY : Oxford University Press, 2019)
"This book tells the story of how families separated across borders write--and learn new ways of writing--in pursuit of love and money. According to the UN, 244 million people currently live outside their countries of birth. The human drama behind these numbers is that parents are often separated from children, brothers from sisters, lovers from each other. Migration, undertaken in response to problems of the wallet, also poses problems for the heart. Writing for Love and Money shows how families separated across borders turn to writing to address these problems. Based on research with transnational families in Latin America, Eastern Europe, and North America, it describes how people write to sustain meaningful relationships across distance and to better their often impoverished circumstances. Despite policy makers' concerns about "brain drain," the book reveals that immigrants' departures do not leave homelands wholly educationally hobbled. Instead, migration promotes experiences of literacy learning in transnational families as they write to reach the two life goals that globalization consistently threatens: economic solvency and familial intimacy." --
"Based on research with transnational families in Latin America, Eastern Europe, and North America, Writing for Love and Money tells the story of how families separated across borders write--and learn new ways of writing--in pursuit of love and money"--
Machine generated contents note: -- Preface -- Introduction: Literacy Learning in Immigrants' Homelands -- Chapter One: What's New about Writing for Love and Money? -- Chapter Two: Writing for Love and Money on Three Continents -- Chapter Three: Learning to Log On: From Post to Internet in Brazil -- Chapter Four: Learning Languages: From Soviet Union to European Union in Latvia -- Chapter Five: Teaching Homeland Family: Love and Money in the U.S. -- Conclusion: Migration-Driven Literacy Learning in Uncertain Times -- Afterword: The Mothers.
Includes bibliographical references and index.
Keywords: Literacy -- Social aspects; Immigrants -- Correspondence; Letter writing -- Social aspects; Written communication -- Social aspects; LANGUAGE ARTS & DISCIPLINES / Linguistics / Sociolinguistics; EDUCATION / Philosophy & Social Aspects; SOCIAL SCIENCE / Emigration & Immigration